A Team of Instructors’ Use of Social Presence, Teaching Presence, and Attitudinal Dissonance Strategies: An Animal Behaviour and Welfare MOOC - Watson, Sunnie Lee; Watson, William R.; Janakiraman, Shamila; Richardson, Jennifer (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2017)
This case study examined a team of instructors’ use of social presence, teaching presence, and attitudinal dissonance in a Massive Online Open Course (MOOC) on Animal Behaviour and Welfare (ABW), designed to facilitate attitudinal learning. The study reviewed a team of six instructors’ use of social presence and teaching presence by applying the Community of Inquiry (CoI) framework, as well as the establishment of attitudinal dissonance within the announcements and discussion forums. The instructors entered the MOOC as a collaborative facilitation team and created a highly balanced manner of communication and positive atmosphere within the course. The instructional design focused on creating an informative and knowledgeable network of global learners that would agree that animal welfare was a critical social issue in today’s society. These course goals and facilitation intentions were demonstrated through a high number of social and teaching presence indicators, with a significant use of all social presence, teaching presence, and attitudinal dissonance categories in evidence. The results present a review of an instructional team’s facilitation that focused on shaping attitudes about the topic of animal behaviour and welfare within a MOOC. We conclude by providing insights into instructional design and facilitation of MOOCs in general or attitudinal learning specifically.